2016
DOI: 10.1152/ajpregu.00328.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increase in cholinergic modulation with pyridostigmine induces anti-inflammatory cell recruitment soon after acute myocardial infarction in rats

Abstract: -We tested the hypothesis that an increase in the anti-inflammatory cholinergic pathway, when induced by pyridostigmine (PY), may modulate subtypes of lymphocytes (CD4ϩ, CD8ϩ, FOXP3ϩ) and macrophages (M1/M2) soon after myocardial infarction (MI) in rats. Wistar rats, randomly allocated to receive PY (40 mg·kg Ϫ1 ·day Ϫ1 ) in drinking water or to stay without treatment, were followed for 4 days and then were subjected to ligation of the left coronary artery. The groupsdenominated as the pyridostigmine-treated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 42 publications
2
45
0
1
Order By: Relevance
“…Furthermore, targeting nicotinic cholinergic receptor pathways by pharmacologic means or neuromodulation has the added benefit of dampening subsequent systemic inflammatory responses in which cytokines released from damaged tissue promote leukocyte trafficking to the site of injury (3,37,50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, targeting nicotinic cholinergic receptor pathways by pharmacologic means or neuromodulation has the added benefit of dampening subsequent systemic inflammatory responses in which cytokines released from damaged tissue promote leukocyte trafficking to the site of injury (3,37,50).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, vagus nerve stimulation in animal studies and in patients with heart failure has shown improvement in cardiac function, suggesting that cholinergic-pathway activation may provide therapeutic benefit (5,18,45,53,). Other studies using drugs to augment the parasympathetic nervous system or influence vagal tone, including acetylcholinesterase inhibitors such as donepezil or pyridostigmine, show evidence of improved ventricular remodeling and autonomic function in animal models of heart failure or after myocardial infarction (13,26,32,37,42). Studies of patients treated with these drugs for Alzheimer's dementia have reported reduced adverse cardiac events, including myocardial infarction and death (31).…”
mentioning
confidence: 99%
“…53 Several studies reported that AChE inhibitors suppress neurohumoral activation and sympathetic tone, thus improving cardiac autonomic function and cardiac remodelling in MI rats. 28,30,31,36,38,56 Similarly, pyridostigmine increased baroreflex sensitivity in MI rats. It has been shown that the high frequency (HF) component is a marker of parasympathetic tone, whereas the low frequency (LF) component is considered a marker of sympathetic and parasympathetic activity.…”
Section: Of 24mentioning
confidence: 92%
“…85 Innate and adaptive immune cells are involved in initiating the wound healing process. 28 Moreover, treatment with pyridostigmine for 7 days following MI, substantially augmented the M2-macrophages in the left ventricle, while, recruitment of regulatory T lymphocytes was not observed at the 7-day time point following MI. On the other hand, M2-macrophages with an anti-inflammatory profile predominate after 5 days.…”
Section: Models Of Hfmentioning
confidence: 93%
See 1 more Smart Citation